Phonological Acquisition through Pop-Up Book Media in Children with Autism at SLB Mutiara Kasih Plemahan Kediri - Heny Sulistyowati; Akhmad Sauqi Ahya; Ana Fauziah; Natasya Ingga Felani Fauzi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
Language is the main means of communication in human life in this world, whether in writing, orally, or only in the form of certain symbols. Language acquisition takes place in the brain when acquiring the first language or mother tongue. People can experience difficulties in acquiring language due to several things, one of which is in children with special needs, namely autism. This study aims to obtain the results of language acquisition by using pop-up books as media for autistic children in SLB Mutiara Kasih Plehaman Kediri. The benefit of this research is to find out the language acquisition spoken by autistic children using pop-up book media. This study uses a qualitative descriptive method to identify the speech acquisition of autistic childrenusing pop-up books. The source of data in this study is mild autistic students at SLB Mutiara Kasih Plemahan Kediri. Data collection was done by observation, object determination, recording, data transcription, data identification, and codification. Vocabulary in the category of pronounced nouns include ([b,u], [u,r,u]) , [e,e,a,t,u]. [t,o,m,p,e,t], [u,m,i], [l,u], [n,y,e,t], [h,a,r,i], [o,l.a.h] [u,a,n], and ([u,r,a] [u,r,a]).